Effect of Health Education via Mobile Application in Promoting Quality of Life Among Asthmatic Schoolchildren in Urban Malaysia During the COVID-19 Era: A Quasi-experimental Study. Issue 9 (3rd September 2022) - Al Raimi, Abdulaziz Mansoor; Chong, Mei Chan; Tang, Li Yoong; Chua, Yan Piaw; Al Ajeel, Latifa Yahya
Abstract : Bronchial asthma among children is a common chronic disease that may impact quality of life. Health education is one of the strategies to improve knowledge and quality of life. This study aims to assess the effect of health education via a mobile application in promoting the quality of life among schoolchildren with asthma in urban Malaysia during the COVID-19 era. A quasi-experimental, pre- and post-intervention design was used in this study involving a total of 214 students, randomly assigned into two groups (an intervention group and a control group). The control group received face-to-face health education, whereas the experimental group received health education via a mobile application. The findings showed that the total score of quality of life improved from a mean total score at pre-intervention of 5.31 ± 1.27 to post-intervention of 5.66 ± 1.28 for the control group, compared with the experimental group with a mean total score of quality of life at pre-intervention of 5.01 ± 1.36 and post-intervention of 5.85 ± 1.29. A comparison between the experimental and control groups using an independent t test showed statistically significant differences in their mean quality of life scores. The effect of health education via a mobile application showed a statistically significant improvement in the mean quality of life score from pre- to post-intervention ( F 1, 288 = 57.46, P < .01). As recommended, the use of mobile technology in health education improved the quality of life of schoolchildren with asthma as compared with the traditional methods of a face-to-face lecture and/or a handbook. Thus, educational modules using mobile applications do improve quality of life.